Masculinity from the perspective of men with intellectual disability - Gutowska, Anna (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
Current scientific publications present different paradigms of masculinity, but research in this area is a relatively new perspective. However, the specific nature of the everyday experience of people with intellectual disability is still neglected and unrecognised. The aim of this article is to show the concept of masculinity from the perspective of men with intellectual disability. The research is placed in the stream of qualitative research using a case study as a method. The subject of the research covers the statements of men with intellectual disability concerning masculinity. The analysis of the research material obtained from 12 interviews allowed for the identification of four types of masculinity.